2021
DOI: 10.13083/reveng.v29i1.11758
|View full text |Cite
|
Sign up to set email alerts
|

Development of soybean genotypes as a function of water availability and sowing seasons in Rio Verde, state of Goias

Abstract: Soybean crop yield is affected in the absence of favorable conditions for its complete development, and one of the most limiting factors is the water availability throughout the crop cycle. Therefore, the objective of this study was to evaluate the behavior of three soybean genotypes, in two sowing dates, during two harvests, in the city of Rio Verde, Stat of Goiás. Four experiments were carried out in a randomized block design, with four replicates in the 2018/2019 and 2019/2020 harvests. The variables analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…Com a ausência de precipitação, a intensidade de radiação solar e a temperatura do ar são maiores, porém, os sistemas de irrigação amenizam ao menos a temperatura do solo, propiciando a melhores condições de desenvolvimento as culturas, questão essa muitas das vezes negligenciadas pelos agricultores. Na região em estudo, há uma incompatibilidade entre o término do vazio sanitário e início do período chuvoso, chegando há uma variação de até 40 dias, na média conforme Soares et al (2021). De acordo com os mesmos autores, o período seguro para cultivo de soja na região de Rio Verde em condições de sequeiro é de 20 de outubro a 20 de novembro para genótipos de ciclo de 120 dias, enquanto o vazio sanitário termina no dia 2 de setembro.…”
Section: Introductionunclassified
“…Com a ausência de precipitação, a intensidade de radiação solar e a temperatura do ar são maiores, porém, os sistemas de irrigação amenizam ao menos a temperatura do solo, propiciando a melhores condições de desenvolvimento as culturas, questão essa muitas das vezes negligenciadas pelos agricultores. Na região em estudo, há uma incompatibilidade entre o término do vazio sanitário e início do período chuvoso, chegando há uma variação de até 40 dias, na média conforme Soares et al (2021). De acordo com os mesmos autores, o período seguro para cultivo de soja na região de Rio Verde em condições de sequeiro é de 20 de outubro a 20 de novembro para genótipos de ciclo de 120 dias, enquanto o vazio sanitário termina no dia 2 de setembro.…”
Section: Introductionunclassified
“…occurring, on average, until november 20th Soares et al (2021),. evaluating several soybean genotypes and their performance depending on the availability of water stored in the soil, concluded that sowing the soybean crop (120 days) in a period with favorable water availability for the plant's performance during its cycle occurs in october 20th to november 20th in the Rio Verde region.…”
mentioning
confidence: 99%